Early detection of pregnancy after IVF and embryo transfer with hyperglycosylated HCG versus Elecsys HCG+β assay. Issue 2 (February 2022) - Bosch, Ernesto; Hund, Martin; van der Does, Reinhard; Caracena, Laura; Ahlers, Silke; Labarta, Elena
HIGHLIGHTS: hHCG and HCG+β measured at Day 4 after IVF-ET may aid early pregnancy detection. hHCG and HCG+β had similar predictive performance when measured at Day 4, 7 and 11. Performance of hHCG and HCG+β improved from Day 4 to 7 and Day 7 to 11 post-IVF-ET. Superiority of hHCG over HCG+β was not shown. Abstract: Research question: Is measurement of hyperglycosylated HCG (hHCG) superior to beta-HCG (HCG+β) for early pregnancy detection after IVF and embryo transfer? Design: Blood samples were collected on day 4 (+1), 7 (+1) and 11 (+2) after embryo transfer from women aged 18–45 years undergoing first or second fresh or frozen IVF embryo transfer cycles. Biochemical pregnancy was assessed on-site by HCG determination on day 11; clinical pregnancy was assessed by ultrasound on day 21 (+4/–3). Serum hHCG (immunochemiluminometric assay) and HCG+β (Elecsys® HCG+β assay) concentrations were measured. Performance of hHCG and HCG+β for predicting pregnancy was evaluated and cut-offs selected. Results: In total, 155 women were enrolled and underwent IVF and embryo transfer. Area under the curve (AUC) (95% CI) on day 4 was not significantly different for hHCG (AUC 0.88; 95% CI 0.83 to 0.94) and HCG+β (AUC 0.90; 95% CI 0.84 to 0.95), as was predictive performance on day 7 and 11, with higher AUC estimates compared with day 4. Applying cut-offs derived according to Youden's index on day 4 (hHCG, 100 pg/ml; HCG+β, 1.30 mIU/ml), both biomarkers demonstrated high negative predictive values for ruling out pregnancy (hHCG, 83.8%; HCG+β, 82.8%) and high positive predictive values for ruling in pregnancy (hHCG, 89.0%; HCG+β, 84.9%) on day 21. Diagnostic performance improved from day 4 to day 11. Conclusions: Predictive performance for early pregnancy post-IVF embryo transfer of day-5 blastocysts was not significantly different for hHCG and HCG+β; hHCG superiority over HCG+β was not shown.